P5 Pulmonary hypertension in a mouse model with reduced macrophage number (MacLow). (2nd December 2011) - Zawia, A; Arnold, N; Pickworth, J; Hameed, A; Hopkinson, K; Miller, G; Lawrie, A
Abstract : Introduction and Objectives: Pulmonary arterial hypertension (PAH) is a devastating condition with high morbidity and poor life expectancy. Pathologically PAH is characterised by the medial thickening of the small distal pulmonary arteries. Early endothelial cell (EC) dysfunction and apoptosis, and the subsequent abnormal proliferation and migration of pulmonary artery smooth muscle cells are thought to be a major contributing factor. Macrophages are proposed to play an important role in regulating these processes and are recruited to remodelled pulmonary arteries but the exact role of macrophages, and whether they are required for this remodelling remains unclear. We have recently developed a mouse model ( MacLow ) where approximately 50% of macrophages are depleted and now aim to investigate whether MacLow mice would demonstrate a reduced pulmonary hypertension phenotype in response to hypoxia, when compared to non-macrophage ablated littermates. Methods: Macrophage ablation was induced in CD68-rtTA-eGFP/tetDTA double transgenic mice ( MacLow ) where macrophage-specific (CD68) induction of the cytotoxic diphtheria toxin A chain (DTA) is achieved by administration of doxycycline containing chow diet (doxy-chow). Mice were divided by sex and then fed either regular or doxy-chow for 2 weeks prior to either 2 weeks exposure to hypoxia (10% oxygen), or room air. All mice were phenotyped for PH by echocardiography followed by closed chest cardiac catheterisation. Heart and lung tissue were harvested for morphological, immunohistochemical and biochemical analyses. Results: Doxy-chow fed mice displayed the expected 50% reduction in macrophages (liver) compared to controls. MacLow mice with the induced ablation of macrophages were not protected from hypoxia induced pulmonary hypertension although females displayed a trend for higher RVSP after hypoxia (34 mm Hg vs 29 mm Hg). Interestingly male MacLow mice with induced macrophage ablation displayed a spontaneous PAH phenotype (33 mm Hg), in normoxia, that was not further increased by hypoxia. The changes in RVSP were accompanied by appropriate changes in RVH. Conclusion: These data suggest that macrophages play a modulating role in pulmonary vascular remodelling but further work is required to explore the mechanisms involved in this phenotype, and to fully assess the change in macrophage number within the lungs of these mice.